Pengaruh Supervisi Akademik Kepala Sekolah dan Iklim Organisasi Sekolah terhadap Kinerja Guru - Sumayadi, Ahmad; Permana, Deni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2021)
This research is motivated by the empirical phenomenon of the innovative performance of teachers. Efforts to improve the innovative performance of teachers through the principal's academic supervision and the school's organizational climate have not shown the expected results. The innovative performance of teachers is a demand in justification which is the responsibility of teachers and principals as the locomotive of the school organization. The innovative performance of teachers is influenced by various internal and external factors of the school such as: school climate, school culture, intensity of supervision, academic supervision of principals, educational facilities, principals' leadership, organizational structure and so on. The problem that is the focus of this research study is how the 'Effect of Principal Academic Supervision and School Organizational Climate on Teacher Performance'. This study aims in general to prove the objective conditions of the influence of principal academic supervision and school organizational climate on the innovative performance of teachers in Trimurjo District, Metro City in 2019.